Activating SIRT-1 Signalling with the Mitochondrial-CoQ10 Activator Solanesol Improves Neurobehavioral and Neurochemical Defects in Ouabain-Induced Experimental Model of Bipolar Disorder - Bidisha Rajkhowa; Sidharth Mehan; Pranshul Sethi; Aradhana Prajapati; Manisha Suri; Sumit Kumar; Sonalika Bhalla; Acharan S. Narula; Abdulrahman Alshammari; Metab Alharbi; Nora Alkahtani; Saeed Alghamdi; et al. (MDPI AG, 2022)
Bipolar disorder (BD) is a chronic mental illness characterized by mood fluctuations that range from depressive lows to manic highs. Several studies have linked the downregulation of SIRT-1 (silent mating type information regulation-2 homologs) signaling to the onset of BD and other neurological dysfunctions. This research aimed to look into the neuroprotective potential of Solanesol (SNL) in rats given ICV-Ouabain injections, focusing on its effect on SIRT-1 signaling activation in the brain. Ouabain, found in hypothalamic and medullary neurons, is an endogenous inhibitor of brain Na+/K+ ATPase. The inhibition of brain Na+/K+ ATPase by Ouabain may also result in changes in neurotransmission within the central nervous system. SNL is a Solanaceae family active phytoconstituent produced from the plant Nicotiana tabacum. SNL is used as a precursor for the production of CoQ10 (Coenzyme Q10), a powerful antioxidant and neuroprotective compound. In the current study, lithium (Li), an important mood stabilizer drug, was used as a control. This study looked at the neuroprotective potential of SNL at dosages of 40 and 80 mg/kg in ICV-OUA injections that caused BD-like neurobehavioral and neurochemical defects in Wistar rats. Wistar rats were placed into eight groups (n = 6) and administered 1 mM/0.5 µL ICV-OUA injections for three days. Neurochemical assessments were done in rat brain homogenates, CSF, and blood plasma samples at the end of the experiment protocol schedule. Long-term SNL and lithium administration have been shown to decrease the number of rearing and crossings and reduce time spent in the center, locomotor activities, and immobility time. Solansesol treatment gradually raises the amount of Na+/K+ ATPase, limiting the severity of behavioural symptoms. These findings also revealed that SNL increases the levels of SIRT-1 in CSF, blood plasma, and brain homogenate samples. Moreover, in rat brain homogenates and blood plasma samples, SNL modulates apoptotic markers such as Caspase-3, Bax (pro-apoptotic), and Bcl-2 (anti-apoptotic). Mitochondrial-ETC complex enzymes, including complex-I, II, IV, V, and CoQ10, were also restored following long-term SNL treatment. Furthermore, SNL lowered inflammatory cytokines (TNF-α, IL-1β) levels while restoring neurotransmitter levels (serotonin, dopamine, glutamate, and acetylcholine) and decreasing oxidative stress markers. Histological examinations also validated Solanesol's protective effect. As a result, our findings suggest that SNL, as a SIRT-1 signalling activator, may be a promising therapeutic approach for BD-like neurological dysfunctions.